Analisis SWOT Mutu Evaluasi Pembelajaran - Sodikin, Sodikin; Gumiandari, Septi (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2022)
This research aims to find out the quality of learning evaluation in MTs Negeri 9 Kuningan through SWOT analysis. This study uses qualitative descriptive methods, where data is collected through interview questionnaires with Madrasah Heads and Subject Teachers, students, parents of students / communities as well as evidence of RPP documentation, instrument assessment of both attitude scale and daily reassessment instruments and other support. The results showed that the strength factors of MTs Negeri 9 Kuningan include: the fulfillment of professional teachers, the evaluation system refers to quality standards, high interest and motivation to learn. While the weakness is seen in the existence of some teachers who have not mastered the technology of the IT field, students who are not honest when repeating, students who do not understand how to fill the question of repeat. The opportunities that have been owned are professional teacher certification, the support of the parents of students, support from the surrounding community. While the threat facing there is competition between institutions, students who move to other schools, students who cannot continue to favorite schools. Efforts made to address weaknesses and threats are to optimize the strengths and opportunities they have.